The effect of oligosaccharide chitosan irrigating agent on penetration of two type endodontic sealers into the dentinal tubules: a confocal laser scanning microscopy study - Abidin, Trimurni; Darmawan, Gieska Lailarahma; Dalimunthe, Fatimah Dewi (Faculty of Dentistry Universitas Padjadjaran, 2022)
ABSTRACTIntroduction: Irrigation during root canal treatment is one of the important factors that play a role in determining the quality of sealer penetration into the dentinal tubules, especially in the apical third of the tooth root. This is inseparable from the selection of the used irrigation agent. Currently, oligosaccharide chitosan has been developed which is easier to manipulate as an alternative irrigation agent. This study aimed to analyze the effect of the chitosan oligosaccharide irrigating agent on the penetration of two types of endodontic sealers into the dentinal tubules. Methods: This study used 60 mandibular premolars which were randomly divided into 3 groups (n=3). Group 1 was irrigated with 2% chitosan oligosaccharides; Group 2 with a combination of 2.5% NaOCl and 0.2% chitosan nanoparticles; and group 3 was irrigated with a combination of 2.5% NaOCl and 17% EDTA. At the time of obturation, each group was divided into two groups, for sealer treatment using CeraSeal Bioceramic and AH Plus sealer. The sealer’s penetration depth was measured using a confocal laser scanning microscope. Results: The highest mean on the penetration depth of the sealer was seen in the irrigation group using chitosan oligosaccharide solution with CeraSeal bioceramic sealer (2575,151 AU) (p>0.05). Conclusion: There is an effect of 2% oligosaccharide chitosan solution on sealer penetration into dentinal tubules. CeraSeal bioceramic sealer showed better penetration than AH Plus sealer.Keywords: oligosaccharide chitosan; ceraseal bioceramic sealer; AH plus sealer; confocal laser scanning microscope